Mast cell activation and migration to lymph nodes during induction of an immune response in mice. - Wang, H W (1998)
The mast cell response in skin and lymph nodes was examined during the sensitization phase of dinitrofluorobenzene (DNFB)-induced contact hypersensitivity in mice. Degranulation of 62% of mast cells in DNFB-exposed skin was evident within 30 min of a dual application of DNFB, reaching a peak of 77% at 24 h, and persisting in 42% after 5 d. Abundant expression of macrophage inflammatory protein (MIP)-1alpha and MIP-1beta mRNAs and proteins was observed in keratinocytes, and mast cell degranulation was significantly inhibited after administration of neutralizing antibodies to MIP-1alpha, but not MIP-1beta. During DNFB sensitization, the mast cell density in the skin decreased by half, concurrent with a fivefold expansion of mast cell numbers in draining lymph nodes. Fluorescent-labeled mast cells injected into the skin appeared in draining lymph nodes after application of DNFB, followed by subsequent migration to the spleen. In lymph nodes, mast cells were an abundant and predominant source of MIP-1beta, neutralization of which partially inhibited T lymphocyte recruitment. These results indicate that mast cells contribute to the induction of this primary immune response by activation at and migration from the site of antigen encounter to draining lymph nodes, wherein they mediate T lymphocyte recruitment by production of MIP-1beta.